Disolución conyugal y el desarrollo psicoafectivo en los niños(as) de la Unidad Educativa Cesar Borja Lavayen, año 2019 - Méndez Jaramillo, Diana Kimberly (2019)
In this present investigation, the analysis of the causes of the conjugal dissolution in the psycho-affective development of the children was carried out, as this situation predominates in them, due to the lack of attention, inadequate communication of some parents towards them. to influence development. The presence of domestic violence in which the three types of violence are described, whether psychological, physical or verbal, are those that lead to divorce, and when children (as) involved, we understand that children are the most vulnerable They do not understand the act of their parents, they are afraid of the consequence that surrounds them. The objective of this investigation was in the approach of interventions in cases of conjugal dissolution mostly directed to parents and one or two with the company of their respective children to socialize and understand unknown terms and prevent or reduce the cases of dissolution in the parents of the childre.